Answer:
In the given polynomial p(x)
![Q(x) = (2x^2 + 2x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uvjedspq2g8ocj9pso419ayq33rgsjvh6m.png)
Remainder = p(2) = 7
Explanation:
Here, the given polynomial is
![p(x)=2x^3-2x^2-4x+7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q0j0nf0evl8ng5tv1vl0ca1eq17adsdz7m.png)
Also, p (2) is to be determined,
⇒ x = 2 is the zero of the given p(x)
⇒ (x- 2) is he Root of the polynomial.
Now, by REMAINDER THEOREM:
The remainder theorem states that when a polynomial, f(x), is divided by a linear polynomial , x - a, the remainder of that division will be equivalent to f(a).
So, here when p(x) is divided by ( x- 2) the remainder = p(2)
![(P(x))/((x-2)) = Q(x) + p(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7fyabcmqat4txirmpc26pb983div0q2gtl.png)
Now,
![p(2) =2(2)^3-2(2)^2-4(2)+7 =16 -8-8+7 = 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fgb18hwef2jgdekfkyoeja2g17fipjclwk.png)
⇒ p(2) = 7
Now, the given equation becomes:
Now,
![(P(x))/((x-2)) = Q(x) + 7\\\implies Q(x) = (P(x))/((x-2)) - 7 = (2x^3-2x^2-4x+7)/(x-2) -7\\= (2x^2 + 2x) - 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/peyeeu6xuj12pwespjinnby35op0dxyo8r.png)
![\implies Q(x) = (2x^2 + 2x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ua3p0lra326ru7wzrzhrvxgjosvm50pti7.png)